Optimization in Electrical Engineering - Fathi, Mohammad; Bevrani, Hassan; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This textbook provides students, researchers, and engineers in the area of electrical engineering with advanced mathematical optimization methods. Presented in a readable format, this book highlights fundamental concepts of advanced optimization used in electrical engineering. Chapters provide a collection that ranges from simple yet important concepts such as unconstrained optimization to highly advanced topics such as linear matrix inequalities and artificial intelligence-based optimization methodologies. The reader is motivated to engage with the content via numerous application examples of optimization in the area of electrical engineering. The book begins with an extended review of linear algebra that is a prerequisite to mathematical optimization. It then precedes with unconstrained optimization, convex programming, duality, linear matrix inequality, and intelligent optimization methods. This book can be used as the main text in courses such as Engineering Optimization, Convex Engineering Optimization, Advanced Engineering Mathematics and Robust Optimization and will be useful for practicing design engineers in electrical engineering fields. Author provided cases studies and worked examples are included for student and instructor use.
Introduction -- Linear Algebra Review -- Set constrained Optimization -- Convex Programming -- Duality -- LMI-based Optimization -- Artificial intelligence and evolutionary algorithms based optimization.
Keywords: Electric power production; Mathematical optimization; Electrical Power Engineering; Optimization; Mechanical Power Engineering